Soihet, Raquel. A subversão pelo riso. Rio de Janeiro, Fundação Getúlio Vargas, 1998. 200p. Augras, Monique. O Brasil do samba-enredo. Rio de Janeiro, Fundação Getúlio Vargas, 1998. 296p. - Lima, Ari (Afro-Ásia, 2000)
.